2022
DOI: 10.5371/hp.2022.34.2.96
|View full text |Cite
|
Sign up to set email alerts
|

Dual-mobility versus Fixed-bearing in Primary Total Hip Arthroplasty: Outcome Comparison

Abstract: Purpose Use of dual mobility (DM) articulations can reduce the risk of instability in both primary and revision total hip arthroplasty (THA). Knowledge regarding the impact of this design on patient-reported outcome measures (PROMs) is limited. This study aims to compare clinical outcomes between DM and fixed bearing (FB) prostheses following primary THA. Materials and Methods All patients who underwent primary THA between 2011-2021 were reviewed retrospectively. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
(44 reference statements)
1
4
0
Order By: Relevance
“…The dislocation rate in modDM has been likely influenced by confounding factors such as cup malpositioning or femoral neck fracture, even though the multivariate regression analysis did not show any significant covariate predictive for dislocation. Similar results are reported by Singh et al [ 25 ] who conducted a retrospective propensity score-matched analysis between SB vs monobloc DM vs modular DM. The authors found no statistical difference in the 90-day all-cause revision rate (3.4% vs. 2.7% vs. 0.7%; p = 0.265) and the 90-day revision rate due to dislocation (1.3% vs. 0.7% vs. 0.0%; p = 0.365) between the SB, modular DM, and monobloc DM cohorts, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…The dislocation rate in modDM has been likely influenced by confounding factors such as cup malpositioning or femoral neck fracture, even though the multivariate regression analysis did not show any significant covariate predictive for dislocation. Similar results are reported by Singh et al [ 25 ] who conducted a retrospective propensity score-matched analysis between SB vs monobloc DM vs modular DM. The authors found no statistical difference in the 90-day all-cause revision rate (3.4% vs. 2.7% vs. 0.7%; p = 0.265) and the 90-day revision rate due to dislocation (1.3% vs. 0.7% vs. 0.0%; p = 0.365) between the SB, modular DM, and monobloc DM cohorts, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…Of the 63 articles included, 11 reported outcomes for two different approaches in the same study [ 10 , 33 , 40 , 43 , 49 , 50 , 52 , 69 , 79 , 84 ], and one study reported three approaches [ 74 ], resulting in 75 total study arms. Eight studies reported the DAA, five reported the ALA, six reported the DLA, and 56 studies reported the PLA (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Zero dislocations were reported in 4 of 5 ALA studies (80%), 7 of 8 DAA studies (87.5%), 6 of 6 DLA studies (100%), and 46 of 56 PLA studies (82.1%) (Table 3 ). The two studies with dislocations following DAA and ALA reported rates of 1.8% and 0.9%, respectively [ 84 , 87 ]. The highest dislocation rate for PLA was 4.7% [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are corroborated by those of other studies, where DM implants in the setting of primary THA yield high PROMS. Singh et al compared primary THA patients who received a fixed-bearing, monoblock or modular DM implant and found no difference in PROMs at two years in the DM groups [ 28 ]. Tarazi et al also noted excellent Harris hip scores (HHS) at long-term follow-up (seven years) in patients who received a primary THA with DM liner [ 13 ].…”
Section: Discussionmentioning
confidence: 99%